An overview of financial instruments and capital market operations in Belize - Solis, Laetitia ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1995)
Presents an overview of financial institutions and instruments which currently exist in the domestic market. Examines commercial banks' depoisits; governance securities; equity/debt instruments which evolves through government's privatization activities of the 1980s and early 1990s; and private sector instruments placed on the market to finance specific endeavours. Assesses their financiall assets to determine the extent to which these activities constitute the basis for market development.